Integrated geological and geophysical investigations for the discovery of deeply buried gold–polymetallic deposits in China. (2nd July 2019) - Xue, Guoqiang; Zhang, Linbo; Hou, Dongyang; Liu, Hongtao; Ding, Yunhe; Wang, Chunyong; Luo, Xiaonan
Abstract : Xiaoshan gold–polymetallic concentrated area is located in Henan Province, central China. The area is principally underlain by typical metamorphic core complexes (MCCs), along with essential components of the basins and ranges of western Henan. Mineralization occurs in the regions where the geochemical anomalies of Au and related elements are widely distributed and consist predominantly of mineralized altered rocks and auriferous quartz veins, both of which are hosted within shear zones or fractures of varying sizes and orientations. Several small‐ to medium‐sized gold–polymetallic ore deposits, along with numerous clustered occurrences, have been found in the area in recent years. However, despite the fact that the Xiaoshan District has traditionally been deemed as an excellent geological endowment area with enormous potential for large‐sized deposits, no significant discoveries have been made to date. It is suggested that the main reason responsible for the present exploration situation could be the scarcity of applications of deep‐penetration geophysical prospecting in the area. It is anticipated that integrating geological and geophysical data would be crucial to enhance the successful mineral explorations. In this contribution, a conceptual geological model for the study area was initially reviewed so that the corresponding electromagnetic responses could then be modelled, which would simulate a geophysical type of survey, with appropriate uncertainties added into the analyses. Then, based on such an integrated approach, the required precision of detecting deep‐buried deposits could then be evaluated. In addition, by employing supplementary geophysical data acquired over known deposits, it is possible to gain more instructive insights into the practical geological model. The viabilities of this approach were demonstrated through a case study in which a hidden gold deposit in the studied area was successfully detected. Geophysical surveys were carried out by employing a grounded‐wire short‐offset TEM (SOTEM) technique and revealed two new anomalies (one of which was subsequently tested by drilling). The drilling then confirmed that this anomaly was caused by an ore body 30 m in thickness occurring at about 550 m below surface.